Nurturing Social Trust through Students' Digital Communication Ethics: Sustainable Strengthening Based on Digital Culture - Saddam, Saddam; Winata, Aliahardi; Saoki, Muhamad; Putri, Fina Elisa (IJTIMAIYA: Journal of Social Science and Teaching, 2026)
Digital transformation in higher education expands students' academic communication while also presenting challenges to digital ethics. This study aims to analyze the strengthening of digital communication ethics based on digital culture and its contribution to the formation of social trust. Using a qualitative approach and constructivist grounded theory design, data were obtained through interviews, digital observations, and document analysis. The results show the separation of personal and academic spaces, ethics through reprimands and role models, negotiation of norms across various platforms, and the formation of social trust through consistent communication. The novelty of this study lies in the "corrective habituation based on digital culture" model, which explains the internalization of communication through correction, reflection, habituation, and role models until it becomes a sustainable campus culture. These findings expand the study of digital ethics from a knowledge perspective to a continuous socio-cultural process.